2019
DOI: 10.1002/ctpp.201800001
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐in‐cell simulation of the effect of curved magnetic field on wall bombardment and erosion in a hall thruster

Abstract: A curved, convex towards the channel bottom magnetic field is an important feature of an advanced Hall thruster that allows confining the plasma flow in the channel center, reducing the divergence angle of the ejected ion beam, and improving the discharge performance. In this article, the discharge behaviour of a Hall thruster in magnetic fields with different degrees of curvature is simulated with a particle‐in‐cell numerical method, and the effect of curved magnetic field on the ion bombardment and wall eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Meanwhile, it can be found that the peak erosion rate under the lower and middle gas supply conditions is relatively close, and that the peak erosion rates of the inner and outer walls are about 6.3 mm/kh and 10.7 mm/kh respectively. Considering the order of magnitude, it is consistent with previous literature reports [32]. The peak erosion rate under the upper gas supply condition is relatively low, and the peak erosion rates on the inner and outer walls are 4.2 mm/kh and 7.5 mm/kh respectively, which are 33.3% and 29.9% lower than those under the other two conditions.…”
Section: Wall Erosion Rate Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, it can be found that the peak erosion rate under the lower and middle gas supply conditions is relatively close, and that the peak erosion rates of the inner and outer walls are about 6.3 mm/kh and 10.7 mm/kh respectively. Considering the order of magnitude, it is consistent with previous literature reports [32]. The peak erosion rate under the upper gas supply condition is relatively low, and the peak erosion rates on the inner and outer walls are 4.2 mm/kh and 7.5 mm/kh respectively, which are 33.3% and 29.9% lower than those under the other two conditions.…”
Section: Wall Erosion Rate Distributionsupporting
confidence: 91%
“…In terms of the angle dependence function, we use the Pencil model [8,32,35]; its function form is shown in equation (7). Here, the correlation coefficients are based on the erosion experimental results of BN, c 1 = 0.53, c 2 = 2.61, c 3 = 1.54 [32]. The distribution of the angular sputtering coefficient is shown in figure 3.…”
Section: Wall Erosion Modelmentioning
confidence: 99%
“…Further plasma discharge model fidelity was attained with the advent of particle-in-cell (PIC) models that solve the equations of motion for super particles representing groups of individual particles. Like fluid modelers, most authors [37,[93][94][95][96][97][98] implementing PIC models for erosion calculation relied on simple theoretical fits of experimental data to determine sputtering yield. However, Cheng et al [99] developed a variation of the Yamamura and Tawara model based on physical considerations, and Cao et al [100] utilized the Huygens wavelet method to predict surface evolution.…”
Section: Hall Thruster Erosion Modelingmentioning
confidence: 99%